Prediction of energy absorption capability of curved panel structure; for wing leading edge study - Omar, Norihan; Md Khalid, Nur Aisyah; Shamsudin, Nor Fadilah; Aminanda, Yulfian (Trans Tech Publications Ltd., Switzerland, 2012)
This paper works on the curvature effect of wing leading edge structure subjected to impact loading. At first stage, rigid spherical projectile and semi-elliptical panel were used. The impact testing has been carried out by varying the radius of curvature and the thickness of the panel. The experimental results show the trend of specific energy absorption capability of structure in function of the radius and thickness of panel. From experimental observation, it shows that the failure of structure subjected to impact loading can be distinguished in two types of failure; the projectile went through the structure and large displacement of curved panel. The two failure criteria are used later on to determine the energy absorption capability using Finite Element Analysis method. A FEA model is proposed to simulate the behavior of curved composite structure and validated by the experimental results in order, as final goal, to propose the simulation as a tool of designing the leading edge of wing with an optimum radius curvature and thickness of wing leading edge panel to absorb a specific magnitude of impact energy.